Etika Jawa Kurmat pada Karakter Tokoh Ranggalawe dalam Novel Ranggalawe: Sang Penakluk Mongol (Kajian Sosiologi Sastra) - Desy Proklawati (Departement of Mathematics Education, 2023)
Ranggalawe figures are often used as figures in literary works. The character has an ethic that is loaded with Javanese ethics and can be exemplified from his stories. This study aims to describe the honorable character Ranggalawe in the novel Ranggalawe: the Mongol Conqueror by Makinudin. This research uses a qualitative approach with the type of literary sociology research. The research data is in the form of sentences in the novel with the data source in the form of a novel.